Draft Sikkim Statistical Supplement for Annual Plan 1994-95 Annexure - III (A), (B), (C), and (D) (Volume III) - Planning Commission (Planning Commission, 1993)
Soil and Water Conservation Animal Husbandry and Veterinary Services Fisheries Land Reforms Irrigation Energy Roads and Bridges Transport Tourism Food and Civil Supplies.
Planning and Development Department, Government of Sikkim